Gestión administrativa en el Servicio de Policía Comunitaria del distrito Babahoyo. - Mendieta Torres, Josellyn Isabel (2022)
This case study is called "Administrative management in the community police service of the Babahoyo district" has the objective of analyzing the administrative management in the Community Police Service of the Babahoyo District in the period 2021 and is carried out with the help of the research line of the Commercial Engineering career called Financial, administrative, tax, audit and control management; while the subline is Companies and public and private institutions and the analytical - synthetic and inductive - deductive methods that are implemented with the help of the interview and survey techniques, and their respective interview guide instruments apply to the Coordinator and the survey questionnaire made to the Community Service Police. Therefore, these gave as a result that this police service presents problems such as: defective planning of daily activities, poor management for the allocation of resources, lack of planning in the slogan relays for the establishment of annual vacations, lack of a plan of contingency to cover the positions for eventualities such as accidents, domestic calamity or illness of the police officers, inconsistencies in the assignment of immediate personnel to cover the transfers of police officers to other subzones, lack of external supervision of the fulfillment of the activities in the upc 's and lack of performance evaluation, in conclusion all those refer to the existence of a deficient administrative management that significantly affects the services developed by the institution.